2018
DOI: 10.1242/jcs.216671
|View full text |Cite
|
Sign up to set email alerts
|

p38δ MAPK regulates aggresome biogenesis by phosphorylating SQSTM1 in response to proteasomal stress

Abstract: Aggresome formation is a major strategy to enable cells to cope with proteasomal stress. Misfolded proteins are assembled into micro-aggregates and transported to the microtubule organizing center (MTOC) to form perinuclear aggresomes before their degradation through autophagy. So far, multiple factors have been identified as the activators of micro-aggregate formation, but much less is known about the regulatory mechanisms of their transport. Here, we report that proteasomal stress leads to the activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 35 publications
6
36
0
Order By: Relevance
“…7), further assessing that MKK3-signaling pathway sustains pro-survival effects through the ERCC1-positive regulation. Overall results prompt to support that the MKK3/p38delta MAPK-signaling pathway likely sustains pro-survival effects through ERCC1-positive regulation in CRC cells and suggest that, in line with recent report 25 , the p38delta MAPK isoform represent a key molecular player also in the control of the autophagic process.
Fig. 5MKK3 affects 5-FU efficacy via activation of p38delta MAPK. a , b Western Blot on protein lysates from sh/scr and sh/MKK3 HT29 and SW620 sublines ( a ) and sth/scr and sth/p38δ transfected HT29 and SW620 cells ( b ) either untreated or exposed to 5-FU.
…”
Section: Resultssupporting
confidence: 89%
“…7), further assessing that MKK3-signaling pathway sustains pro-survival effects through the ERCC1-positive regulation. Overall results prompt to support that the MKK3/p38delta MAPK-signaling pathway likely sustains pro-survival effects through ERCC1-positive regulation in CRC cells and suggest that, in line with recent report 25 , the p38delta MAPK isoform represent a key molecular player also in the control of the autophagic process.
Fig. 5MKK3 affects 5-FU efficacy via activation of p38delta MAPK. a , b Western Blot on protein lysates from sh/scr and sh/MKK3 HT29 and SW620 sublines ( a ) and sth/scr and sth/p38δ transfected HT29 and SW620 cells ( b ) either untreated or exposed to 5-FU.
…”
Section: Resultssupporting
confidence: 89%
“…During proteasomal stress, UbK48-linked polyubiquitinated proteins accumulate and package to form aggresome, which are recognized by antibodies. UbK48-positive structures are co-localized with other aggresome markers, such as p62, HDAC6 and PINK1S (13,24,25). To examine the role of just synthesized proteins in aggresome formation, we studied aggresome formation efficiency in MG132-treated cells after blocking transcription by ActD or translation by ANI.…”
Section: Resultsmentioning
confidence: 99%
“…However, some misfolded proteins form dispersed aggregates rather than aggresomes during proteasome inhibition, such as HeLa, Huh7 and Cos7 (55,58). In contrast to aggresomes formed around MTOC, dispersed aggregates are distributed in the cells and do not result in cytoskeleton rearrangements, suggesting that dispersed aggregates may represent intermediate particles during aggresome assembly (24,58). The defects of aggresome formation in these cells may be caused by the lack of critical regulators of aggresome assembly, such as the subtype of p38 kinase (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, TAK1 may also affect p62 body formation through additional modifications since we found that another kinase (TBK1), known to phosphorylate p62 at both Ser‐349 and Ser‐403 , is dispensable for p62 body formation in response to pp242 treatment. It remains unclear whether TAK1 is the kinase directly responsible for p62 phosphorylation or whether it is carried out by kinases acting downstream of TAK1 (such as p38 MAP kinases ). Further study will also be necessary to determine how p62 scaffolds TAK1 activation.…”
Section: Discussionmentioning
confidence: 99%